Monitoring and evaluation in UK low-carbon community groups: benefits, barriers and the politics of the local. Issue 1 (2nd January 2016) - Hobson, Kersty; Hamilton, Jo; Mayne, Ruth
Abstract : In the UK, there now exist hundreds of low-carbon community groups (LCCGs) that aim to decrease collective resource consumption and/or generate renewable energy through diverse social and environmental interventions. These groups have in recent years become the subject of political attention and funding schemes, underpinned by beliefs that LCCGs are key to fostering resilience to climate change and meeting national-level greenhouse gas emission reduction targets. While previous research into LCCGs has focused on drivers, barriers and outcomes of LCCG action, there is now growing policy and academic interest in groups' capacities for, and uses of, monitoring and evaluation (M&E) processes and tools. However, little is known about the experiences, opportunities and potential challenges for LCCGs undertaking M&E. In response, this paper draws on a Knowledge Exchange project that explored M&E processes and tools with a sample of UK LCCGs. It outlines the benefits and drawbacks of groups' attempts to achieve change and to account for their outcomes and/or impacts, individually, and as part of a wider movement. It argues that, while M&E could be one way for groups to "scale up" their impact without losing their grounding in place and community, issues of capacity, resources and utility remain paramount.